Catherine - Lindner, April; Brontë, Emily, 1818-1848. (New York : Little, Brown, 2013)
In this retelling of "Wuthering Heights," Catherine explains how she fell in love with a brooding musician and left her family to return to him, and her daughter describes searching for her mother many years later.
Booklist
Kirkus Review
Booklist, September 2012
Kirkus Review, December 2012
Young Adult.
Young Adult
Keywords: Mothers -- Juvenile fiction; Love -- Fiction; Mothers -- Fiction; Love stories; Mothers -- Fiction; Love stories